Beneficiaries' Satisfaction with the Quality of Health Services: A case Study of Al-Salam University Hospital, River Nile State, Sudan - Abu Elhassan, Yousif Awad-Elkarim; Mohi-Eldin, Mohi-Eldin Ali; Elhadi, Osman Abdalla Mohamed; Gorshi, Eslam Hassan (Journal of Economic, Administrative and Legal Sciences, 2025)
This study aims to assess the level of beneficiaries’ satisfaction with the quality of health services in the inpatient wards, referral clinics, and emergency department of Al-Salam University Hospital in the Nile River State, Sudan. It analyses key influencing factors such as infrastructure, medical staff competence, response speed, and the availability of essential medications and medical services. The study's significance lies in providing recommendations to enhance healthcare quality and strengthen patient trust, thereby assisting policymakers in developing more efficient health policies. A descriptive-analytical approach is employed using the SERVQUAL model, focusing on two main hypotheses: differences in patient satisfaction levels across hospital departments and a statistically significant relationship between service quality and its five dimensions (tangibility, reliability, responsiveness, assurance, and empathy). The findings indicate higher satisfaction levels in the emergency department compared to outpatient and inpatient services, with inadequate ward facilities, insufficient comfort and cleanliness, and variability in responsiveness and reliability across departments. Additionally, the study highlights deficiencies in the availability of medications and medical supplies, with statistically significant differences among departments. The study recommends improving infrastructure and facilities, enhancing response speed, training medical staff, increasing medication availability, and integrating technology into healthcare management to improve service quality and patient satisfaction.
Keywords: beneficiary satisfaction; service quality; Al Salam University Hospital